PARENTAL INVOLVEMENT AND STUDENTS' HOME READING HABITS: EVIDENCE FROM ELEMENTARY SCHOOL LITERACY PRACTICES IN INDONESIA - Irwan Supriadin; Ahmad Syagif Hannany Mustaufy (SENSEI RESEARCH CENTER, 2024)
Reading habit is very important for elementary school students, but many students do not like to read at home because they prefer to play with gadgets. Parents have an important role in this matter. This study discusses the influence of parental involvement on students' reading habits at home. The study used a quantitative approach with a survey and it was supported by interviews. The data were analyzed using correlation and regression. The result shows that parental involvement has a significant influence on students' reading habits. The most important thing is the example of the parents themselves. Therefore, the school should cooperate with the parents so that the reading habit of the students can be better.